2021
DOI: 10.3390/cryst11121537
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Ag Nano Paste Joint and Its Influence on Reliability

Abstract: In this paper, the microstructure of Ag nano paste joint was investigated in pressure-less sintering conditions, and the influence of the microstructure on the joint’s reliability was studied. Firstly, silver nanoparticles (Ag NPs) were synthesized using the redox reaction method. To tightly stack the Ag NPs in nano paste, Ag NPs with sizes of 30~50 nm and submicron-sized Ag particles were mixed. It was found that increasing the sintering temperature or sintering time can reduce the porosity of the bonding lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Numerous attempts have been made to lower the sintering temperature by decreasing the size of the Ag particles, but this approach often leads to the agglomeration of Ag nanoparticles at room temperature during synthesis and storage periods. Moreover, synthesizing Ag nanoparticles with diameters below 20 nm is challenging [ 13 , 14 ]. Recent studies have suggested that adding silver salts, such as AgO and AgC 2 O 4 , to Ag pastes can further decrease the sintering temperature by forming Ag nanoparticles through decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous attempts have been made to lower the sintering temperature by decreasing the size of the Ag particles, but this approach often leads to the agglomeration of Ag nanoparticles at room temperature during synthesis and storage periods. Moreover, synthesizing Ag nanoparticles with diameters below 20 nm is challenging [ 13 , 14 ]. Recent studies have suggested that adding silver salts, such as AgO and AgC 2 O 4 , to Ag pastes can further decrease the sintering temperature by forming Ag nanoparticles through decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…A silver composite paste with micron-sized silver flakes as the skeleton and silver nanoparticles as the binder has been proposed to change the sintering process from being surface diffusion-driven to lattice diffusion-driven to improve the sintering drive [ 2 , 6 , 9 ]. In addition, Tian et al mixed Ag NPs with sizes of 30–50 nm and submicron Ag particles to tightly stack Ag NPs in paste [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the requirements of die-attach technologies and the Restriction of Hazardous Substances (RoHS) directive, a series of die-attach materials, such as Sn-Ag, Sn-Ag-Cu (i.e., SAC) solder alloys and sintering silver paste were developed [7][8][9]. Among them, the SAC solder has become a type of widely used lead-free solder in the electronics industry by the virtue of its adequate thermal fatigue properties, strength, and wettability [10].…”
Section: Introductionmentioning
confidence: 99%